Hydration of Hofmeister ions - Sun, Chang Qing (2020)
Water dissolves salt into ions and then hydrates the ions to form an aqueous solution. Hydration of ions deforms the hydrogen bonding network and triggers the solution with what the pure water never shows such as conductivity, molecular diffusivity, thermal stability, surface stress, solubility, and viscosity, having enormous impact to many branches in biochemistry, chemistry, physics, and energy and environmental industry sectors. However, regulations for the solute-solute-solvent interactions are still open for exploration. From the perspective of the screened ionic polarization and O:H-O bond relaxation, this treatise features the recent progress and a perspective in understanding the hydration dynamics of Hofmeister ions in the typical YI, NaX, ZX2, and NaT salt solutions (Y = Li, Na, K, Rb, Cs; X = F, Cl, Br, I; Z = Mg, Ca, Ba, Sr; T = ClO4, NO3, HSO4, SCN). Phonon spectrometric analysis turned out the f(C) number fraction of bonds transition from the mode of deionized water to the hydrating. The linear f(C) ∝ C form features the invariant hydration volume of small cations that are fully-screened by their hydration H2O dipoles. The nonlinear f(C) ∝ 1 - exp.(-C/C0) form describes that the number insufficiency of the ordered hydrating H2O dipoles partially screens the anions. Molecular anions show stronger yet shorter electric field of dipoles. The screened ionic polarization, inter-solute interaction, and O:H-O bond transition unify the solution conductivity, surface stress, viscosity, and critical energies for phase transition.